Astragenol-3-O-β-D-xylopyranoside, an unusual triterpene type from Ouratea turnarea (Ochnaceae) - Dominique Serge Ngono Bikoboa, Auguste Abouem A Zintchema , b, Joseph Thierry Ndongoa , b, Norbert Mbabi Nyemeck IIa, Gaetan Bayiha Ba Njocka, Fred Zouaa, Paul Mossetc and Dieudonné Emmanuel Pegnyemb (Journal of Applied Pharmaceutical Science, 2013)
Some phytochemical investigations were carried on the roots of Ouratea turnarea. This work led to the isolation of menisdaurin, epicatechin, β-sitosterol-3-O-β-D-glucopyranoside and astragenol-3-O-β-D-xylopyranoside, the last compound is reported for the first time from the Ochnaceae family. Their structures were established by direct interpretation of their spectral data, mainly HRESI-MS, 1D and 2D NMR, and by comparison with literature.
Keywords: Ouratea turnarea, Ochnaceae, triterpene, astragenol, NMR, Chemotaxonomy.